Prefrontal Consolidation and Compensation as a Function of Wearing Denture in Partially Edentulous Elderly Patients - Narita, Noriyuki; Ishii, Tomohiro; Iwaki, Sunao; Kamiya, Kazunobu; Okubo, Masakazu; Uchida, Takeshi; Kantake, Ikuo; Shibutani, Koh (Frontiers in Aging Neuroscience, 2020)
Background The cognitive effects of wearing a denture are not well understood. This study was conducted to clarify the effects of denture use on prefrontal and chewing muscle activities, occlusal state, and subjective chewing ability in partially edentulous elderly individuals. Methods A total of 16 partially edentulous patients were enrolled. Chewing-related prefrontal cortex and jaw muscle activities were simultaneously examined using a functional near-infrared spectroscopy (fNIRS) device and electromyography, under the conditions of unwearing, and wearing a denture. Occlusal state and masticatory score were also determined under both conditions. Using multiple linear regression analysis, associations between prefrontal and chewing activities with wearing were examined using change rates. Results Chewing rhythmicity was maintained under both conditions. As compared with unwearing, the wearing condition was associated with improved prefrontal cortex and chewing muscle activities, occlusal state in regard to force and area, and masticatory score. Also, prefrontal activities were positively associated with burst duration and peak amplitude in masseter (Mm) and temporal muscle activities, as well as masticatory scores. In contrast, prefrontal activities were negatively associated with occlusal force. Conclusion Wearing a denture induced a positive association between burst duration and peak amplitude in Mm and temporal muscle activities and prefrontal activity, which may indicate a parallel consolidation of prefrontal cortex and rhythmical chewing activities, as well as masticatory scores. On the other hand, denture use induced a negative association of occlusal force with prefrontal activities, which might suggest that prefrontal compensative associations for the physiocognitive acquisition depended on biomechanical efficacy gained by wearing a denture.